The 3 May 2006 (Mw 8.0) and 19 March 2009 (Mw 7.6) Tonga earthquakes: Intraslab compressional faulting below the megathrust. Issue 9 (12th September 2015) - Meng, Qingjun; Heeszel, David S.; Ye, Lingling; Lay, Thorne; Wiens, Douglas A.; Jia, Minghai; Cummins, Phil R.
Abstract: The Tonga subduction zone is among the most seismically active regions and has the highest plate convergence rate in the world. However, recorded thrust events confidently located on the plate boundary have not exceeded Mw 8.0, and the historic record suggests low seismic coupling along the arc. We analyze two major thrust fault earthquakes that occurred in central Tonga in 2006 and 2009. The 3 May 2006 Mw 8.0 event has a focal mechanism consistent with interplate thrusting, was located west of the trench, and caused a moderate regional tsunami. However, long‐period seismic wave inversions and finite‐fault modeling by joint inversion of teleseismic body waves and local GPS static offsets indicate a slip distribution centered 65 km deep, about 30 km deeper than the plate boundary revealed by locations of aftershocks, demonstrating that this was an intraslab event. The aftershock locations were obtained using data from seven temporary seismic stations deployed shortly after the main shock, and most lie on the plate boundary, not on either nodal plane of the deeper main shock. The fault plane is ambiguous, and investigation of compound rupture involving coseismic slip along the megathrust does not provide a better fit, although activation of megathrust faulting is responsible for the aftershocks. The 19 March 2009 Mw 7.6 compressional faulting event occurred below the trench; finite‐fault and W‐phase inversions indicate an intraslab, 50 km deep centroid, with ambiguous fault plane. This event also triggered small megathrust faulting. There continues to be a paucity of large megathrust earthquakes in Tonga. Key Points: The Mw 8.0 2006 and Mw 7.6 2009 Tonga compressional earthquakes were intraslab ruptures Both events activated aftershocks on the megathrust and near the trench Regional interplate coupling in southern Tonga appears to be low, with few large thrust earthquakes